Novel MOF-Derived carbon-embedded acicular mullite for efficient removal of bisphenol A and 17α-ethinylestradiol: adsorption mechanisms and thermodynamic studies - Deyong, Liu; Guangcheng, Xiong; Xingcan, Xu; Qi, Xu; Lisheng, Liu; Chu, Wang; Qiuhong, Zhou (Frontiers in Environmental Science, 2025)
Efficient removal of environmental endocrine disruptors (EDCs) from water is crucial for both human health and aquatic ecosystems security. In this study, MOFs were successfully loaded into granular acicular mullite, and then carbonized to synthesize MOF-derived carbon embedded granular acicular mullite (MOF-M-C). The SEM, FTIR, XPS, TGA were used to characterize the modified ceramsite. The adsorption performance of MOF-M-C for BPA and EE2 in aqueous solutions was systematically evaluated through batch experiments, investigating parameters such as contact time, temperature, pH, ionic strength, and coexisting anions. Kinetic, thermodynamic, and isotherm models were applied to analyze the adsorption mechanism. Results showed that the loading capacity of MOFs derived carbon on acicular mullite was 11.81% (w/w). The adsorption kinetics revealed that the process follows a pseudo-second-order model, indicating chemisorption as the dominant mechanism. In the single system, the adsorption capacity for BPA by MOFs derived carbon (MOF-CB) and the MOF-M-C were 51.704 and 71.68 mg·g−1, respectively. While for EE2, the values were 85.414 and 53.78 mg·g−1, respectively. In the binary system, EE2 and BPA competed for adsorption sites, with EE2 showing stronger affinity due to its higher hydrophobicity. Thermodynamic analysis confirmed that the adsorption was spontaneous, endothermic, and entropy-driven. The material’s performance was minimally affected by pH and ionic strength, making it robust for practical applications. Additionally, MOF-M-C demonstrated excellent regeneration efficiency, retaining over 80% of its adsorption capacity after four cycles. These findings highlight MOF-M-C as a promising, reusable adsorbent for the effective removal of endocrine-disrupting compounds from water.